2022
DOI: 10.1177/0958305x221088113
|View full text |Cite
|
Sign up to set email alerts
|

Chemical reaction and thermal characteristiecs of Maxwell nanofluid flow-through solar collector as a potential solar energy cooling application: A modified Buongiorno's model

Abstract: Solar collectors absorb solar radiation at the focus of solar concentrating systems as heat energy which is further transferred to nanofluid. Entropy creation in Maxwell nanofluid flow over an infinite horizontal surface of a porous media is the subject of the current investigation. A non-linear stretching surface then induces a parabolic trough solar collector (PTSC) flow. The thermal boundary layer is studied using a modified version of Buongiorno's Model. As a result, the PDEs, which encompass the physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…When considerations are made on more physical surroundings and remaining industrial difficulties that need to be solved, various hybrid nanofluid combinations can be produced in the future to achieve heat transmission rates for overcoming challenges. The shooting method could be applied to a variety of physical and technical challenges in the future. …”
Section: Discussionmentioning
confidence: 99%
“…When considerations are made on more physical surroundings and remaining industrial difficulties that need to be solved, various hybrid nanofluid combinations can be produced in the future to achieve heat transmission rates for overcoming challenges. The shooting method could be applied to a variety of physical and technical challenges in the future. …”
Section: Discussionmentioning
confidence: 99%
“…[70][71][72][73][74][75][76][77][78][79][80] Some recent developments exploring the significance of the considered research domain are reported by. [81][82][83][84][85][86][87][88][89][90][91][92]…”
Section: Discussionmentioning
confidence: 99%
“…7080 Some recent developments exploring the significance of the considered research domain are reported by. 8192…”
Section: Discussionmentioning
confidence: 99%
“…Future applications of the Galerkin finite element algorithm (G-FEA) could include a range of physical and technological difficulties 11,[50][51][52][53][54][55][56][57][58][59] . According to [60][61][62][63][64][65][66][67][68][69][70] , there have been several recent advancements that explore the importance of the research domain under consideration.…”
Section: Core Points and Conclusionmentioning
confidence: 99%